Peningkatan Kepuasan Belajar Mahasiswa Melalui Program Pembelajaran Luar Kampus - Suratmi Suratmi; Heny Ekawati; Aprelia Afidatul Hanafi; Inta Susanti; Rizky Asta Pramestirini (Jurnal Keperawatan Silampari, 2022)
This study aims to examine the learning satisfaction of 2000 study program students at the University of Muhammadiyah Lamongan through the Merdeka Learning Program at the Merdeka Campus (MBKM). This type of research is quantitative, using an explanatory survey design. The results showed that 49% of students had high satisfaction with off-campus learning programs, 31% of students had moderate pleasure, and 20% of students had low satisfaction. In conclusion, student satisfaction with the MBKM program is high with the fulfillment of each dimension of happiness. Completing each component of joy has a significant role in implementing the MBKM program in meeting the goal of producing competent graduates. Keywords: Learning Objectives, MBKM, Off-campus Learning